PDE4B as a microglia target to reduce neuroinflammation. Issue 10 (1st April 2016) - Pearse, Damien D.; Hughes, Zoë A.
Abstract : The importance of microglia in immune homeostasis within the brain is undisputed. Their role in a diversity of neurological and psychiatric diseases as well as CNS injury is the subject of much investigation. Cyclic adenosine monophosphate (AMP) is a critical regulator of microglia homeostasis; as the predominant negative modulator of cyclic AMP signaling within microglia, phosphodiesterase 4 (PDE4) represents a promising target for modulating immune function. PDE4 expression is regulated by inflammation, and in turn, PDE4 inhibition can alter microglia reactivity. As the prototypic PDE4 inhibitor, rolipram, was tested clinically in the 1980s, drug discovery and clinical development of PDE4 inhibitors have been severely hampered by tolerability issues involving nausea and emesis. The two PDE4 inhibitors approved for peripheral inflammatory disorders (roflumilast and apremilast) lack brain penetration and are dose‐limited by side effects making them unsuitable for modulating microglial function. Subtype selective inhibitors targeting PDE4B are of high interest given the critical role PDE4B plays in immune function versus the association of PDE4D with nausea and emesis. The challenges and requirements for successful development of a novel brain‐penetrant PDE4B inhibitor are discussed in the context of early clinical development strategies. Furthermore, the challenges of monitoring the state of microglia in vivo are highlighted, including a description of the currently available tools and their limitations. Continued drug discovery efforts to identify safe and well‐tolerated, brain‐penetrant PDE4 inhibitors are a reflection of the confidence in the rationale for modulation of this target to produce meaningful therapeutic benefit in a wide range of neurological conditions and injury. GLIA 2016;64:1698–1709 Main Points: Cyclic AMP is a critical regulator of microglial cell homeostasis, its hydrolysis by PDE4B is one of the triggers for neuroinflammation. PDE4B is a promising drug target for modulating microglia reactivity, though efforts remain ongoing to identify safe and well‐tolerated, brain‐penetrant PDE4 inhibitors for clinical use.